Land Suitability and Economic Feasibility Analysis of Peanuts (Arachis hypogaea) in Jatinangor Subdistrict, West Java Province - Devnita, Rina; Solihin, Muhammad Amir; Sandrawati, Apong; Sitorus, Hasnan Pratama (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2024)
Jatinangor Subdistrict in West Java Province has potentiality to be grown by peanuts (Arachishypogaea) due to the proper climate and the quite spacious availabity land. The farmers in this areaare also used to grow this legume and the demand for this commodity increases by years. The objectiveof this study was to evaluate actual land suitability classes and economic feasibility of peanuts inJatinangor Subdistrict. The methodology using survey method following by sampling and laboratoryanalyses to evaluate land suitability. The assessment used matching table considering the limitingfactor for evaluating land suitability. The economic feasibility using R/C ratio (Revenue Cost Ratio).The results showed that the actual land suitability class for peanuts class S3 (Marginal Suitable) withthe limiting factors of water availability, organic carbon content and slope. Non suitable also foundwith limiting factors of coarse material and slope. The R/C ratio for peanuts was 1.52, indicating thatpeanuts were feasible and profitable to cultivate in Jatinangor Subdistrict.